A Holistic Review on Ethosome A Promising Drug Delivery System for Topical Fungal Disease - Dhurve, Roshni (International Journal of Pharmaceutical & Biological Archive, 2015)
A Holistic Review on Ethosome A Promising Drug Delivery System for Topical Fungal Disease